2018
DOI: 10.1097/md.0000000000013691
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of intraosseous mucoepidermoid carcinoma of the mandible

Abstract: Rationale:Mucoepidermoid carcinoma (MEC) is the most common primary salivary gland malignancy. Ectopic MEC can occur in any part of the body, however, only 2% to 4% of MEC could be detected in the jaw, which is named intraosseous mucoepidermoid carcinoma (IMC). IMC is usually a low-grade carcinoma. Uni- or multilocular radiographic lesions should be differential diagnosed with ameloblastoma, odontogenic cysts, and glandular odontogenic cyst (GOC). Radical surgery may prefer for a favorable prognosis. Whereas I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
9
0
9
Order By: Relevance
“…A positive mucin stain is also diagnostic for intraosseous mucoepidermoid carcinoma [ 11 ]. Fusion of TORC1/MAML2 and MECT1:MAML2 genes in intraosseous mucoepidermoid carcinoma was reported by studies by Li et al [ 7 ] and Brookstone and Huvos [ 8 ] and thus they can be used as tumor markers. Intraosseous mucoepidermoid carcinoma can metastasize to the surrounding lymph nodes but rarely to the lung, skin, breast, and cervix [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A positive mucin stain is also diagnostic for intraosseous mucoepidermoid carcinoma [ 11 ]. Fusion of TORC1/MAML2 and MECT1:MAML2 genes in intraosseous mucoepidermoid carcinoma was reported by studies by Li et al [ 7 ] and Brookstone and Huvos [ 8 ] and thus they can be used as tumor markers. Intraosseous mucoepidermoid carcinoma can metastasize to the surrounding lymph nodes but rarely to the lung, skin, breast, and cervix [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 89%
“…As it can be easily misdiagnosed as ameloblastoma, keratocystic Odontoceti Christmas tumor, glandular odontogenic cyst, or malignant salivary gland tumor, we must look for some important characteristic features of this tumor, including: (1) the lesion should have an epithelial and a mucinous component; (2) bone margin destruction and cortical bone expansion may be seen; (3) cortical plates are intact; (4) absence of an accompanying lesion in the salivary gland; (5) exclusion of any other primary tumor, the histology of which could resemble the central tumor, and (6) histopathological findings confirming the tumor [ 6 ]. Radiologically, a CT scan is the preferred diagnostic modality as it provides information on the extent and size of the tumor [ 7 ]. Brookestone and Huvos proposed a three-grade system for the classification of intraosseous mucoepidermoid carcinoma: grade 1- lesions without cortical plate expansion or rupture, grade 2 - lesions with cortical plate expansion but not rupture, and grade 3 - lesions with cortical plate rupture and metastasis to nodes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et all. (10) have reported that low-grade lesions generally (%76.2) display symptoms and in addition, the swelling is %91.1 of all symptoms. Generally, high-grade lesions show many different symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, adjuvant therapy is indicated in the presence of positive margins, metastasis to the lymph nodes, or residual disease (18). The latest review of Li et al (10) reported that %33.3 of high-grade MEC were performed only in surgery and %60 of them were operated on surgery + radiotherapy. The local recurrence rate may be reduced by aggressive surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there may be a potential for the development of an intraosseous mucoepidermoid carcinoma [12], usually derived from the mucus cells that may be present in the dentigerous cyst lining [13,14].…”
Section: Discussionmentioning
confidence: 99%